HGD: an integrated homologous gene database across multiple species. Issue Volume 51:Issue D1(2023) (1st November 2022) - Duan, Guangya; Wu, Gangao; Chen, Xiaoning; Tian, Dongmei; Li, Zhaohua; Sun, Yanling; Du, Zhenglin; Hao, Lili; Song, Shuhui; Gao, Yuan; Xiao, Jingfa; Zhang, Zhang; et al.
Abstract: Homology is fundamental to infer genes' evolutionary processes and relationships with shared ancestry. Existing homolog gene resources vary in terms of inferring methods, homologous relationship and identifiers, posing inevitable difficulties for choosing and mapping homology results from one to another. Here, we present HGD (Homologous Gene Database, https://ngdc.cncb.ac.cn/hgd ), a comprehensive homologs resource integrating multi-species, multi-resources and multi-omics, as a complement to existing resources providing public and one-stop data service. Currently, HGD houses a total of 112 383 644 homologous pairs for 37 species, including 19 animals, 16 plants and 2 microorganisms. Meanwhile, HGD integrates various annotations from public resources, including 16 909 homologs with traits, 276 670 homologs with variants, 398 573 homologs with expression and 536 852 homologs with gene ontology (GO) annotations. HGD provides a wide range of omics gene function annotations to help users gain a deeper understanding of gene function.